Ownership Structure and Firm Performance: Evidence from Jordan - DAKHLALLH, MOHAMMAD MUSTAFA; RASHID, NORFADZILAH; ABDULLAH, WAN AMALINA WAN; DAKHLALLH, ABDALRAHMAN MUSTAFA (The journal of contemporary issues in business and government, 2021)
Previous studies dealing with corporate governance mechanisms testified to the high significance that provided some new direction. The aim of the study was to participate in these directions by presenting empirical evidence relating to the relationship between the ownership structure and firm performance in developing countries like Jordan. To estimate data for the period 2009 to 2017 for a selection of 180 companies listed on the Amman Stock Exchange (ASE), we used management ownership, government ownership, family ownership, institutional ownership and block ownership to provide a comprehensive guide to the ownership structure of Jordanian companies, while we estimated the firm performance through Tobin’s Q (TQ) model. Furthermore, we employed an econometrics procedure such as crossectional dependency test, Panel unit root test (Levin-Lin-Chu (LL) test, Im-Pesaran, Madalla and Wu test and CIPS panel unit root test), Pedroni Cointegration test, System GMM and Pool Mean Group estimates. a balanced panel data method. The results of the four-panel unit root test show that the ownership structure mechanisms have stationary at the first difference, also the results of the Pedroni Cointegration test reveal that ownership structure mechanisms and firm performance have a long-run relationship. Likewise, Process GMM and PMG findings show that ownership structure processes have a significant effect on the performance of the firm estimated by (TQ). The results of this study indicate that empirical studies continue to find a perfect measurement of performance in order to achieve a real type of performance of the firm. The results of the current examination thus provide objective evidence to managers and stakeholders to assist them in their decision.